The influence of associativity in the development of productive opportunities: the case of four agricultural associations in the Moquegua region - Peru - Bobadilla Díaz, Percy (2019)
This article is based on the results of the diagnosis elaborated as part of the course «Field Practice» of Sociology of the Faculty of Social Sciences of the PUCP in the 2018-2 semester. It begins with a theoretical approach on associativity and small agriculture. A mixed methodology is proposed, collecting the perception of actors from the public, private and academic sectors, regarding the importance of this mechanism for the insertion of four agricultural associations of the Moquegua region in national and international markets. From the analysis of associativity and its relationship with capital - human, social, natural, physical, and financial - it is concluded that it functions as a driver of productive opportunities, but still faces challenges to make it a real option in the strengthening of small producers in Moquegua. In particular for the associations studied, natural capital (water or land) is a key factor for associativity, tradition and culture (social capital) serve as ties that foster trust in the group, and market opportunities supported by external agents that enhance the willingness to cooperate and associate. Finally, the institutional framework and the management capacity of these economic units will be decisive for considering associativity as a sustainable and development strategy for small producers.